Тенденції та особливості формування оборотних активів підприємств роздрібної торгівлі - Власова, Наталія Олексіївна; Михайлова, Олена Валентинівна (Харківський державний університет харчування та торгівлі, 2015)
Досліджено динаміку та склад оборотних активів на рівні вибіркової сукупності підприємств роздрібної торгівлі міста Харкова, що дало можливість визначити динамічні зміни та особливості формування в різних за розміром і місцем розташування підприємств, виявити найбільш проблемні місця в їх забезпеченні відповідними ресурсами.

Macroeconomic and mezoeconomic indices in whole characterize peculiarities of formation and general changes in the retail trade circulating assets. Usage of these indices and branch tendencies of separate enterprise’s development can be connected with the difficulties while investigating economic phenomena and processes, their diversity and ambiguity. Therefore, to make researches more detailed one should take into account separate level of the enterprises in branch where formation of circulating assets is made. The goal of this article is to determine modern tendencies of the development, peculiarities of circulating assets structure on retail trade enterprises’ level and degree of their provision with this type of resource, by means of statistic and financial information. Two groups differing by the area and location of enterprises (200 to 500 m² shall be the first group; 200 to 7000 m² shall be the second group) are studied. Evaluation of circulating assets’ formation resulted in the following: – in the first group circulating assets prevail in currency of the balance – up to 70% (non-circulating assets are engaged at the expense of rent). In the second group most of the enterprises also form non-circulating assets at the expense of rent, but 30% of them have their own non-circulating assets that reduces specific weight of circulating assets in currency of the balance; – more liquid content of circulating assets is in the second group, and higher provision of stock rotation is in the first group; – average indices of stock of goods in the first group almost twice exceed the ones in the second group; – the first group in the period of research is characterized by the lost of stock of goods and growth of accounts receivable. The second group has opposite characteristics – reduction of paying capacity of the population stimulates growth of supplies and lowers the goods component of accounts receivable; – high business reputation of large enterprises (the second group) raises their facilities in cooperation with suppliers and other contracting parties that allows to stabilize goods supplies and reduce insurance and stock of goods in whole, arrange supply "just-in-time". The results of the performed research prove some peculiarities of circulating assets’ size and structure formation in different size groups of retail trade enterprises which undoubtedly influence the effectiveness of their functioning and which are to be taken into account in the process of making managerial decisions.
Tendencies and peculiarities of the circulating assets formation in the retail trade enterprises
Keywords: показники; структура; стан; динаміка; платоспроможні покупці; прийняття управлінських рішень; index; structure; state; dynamics; peculiarities of formation